EFEKTIVITAS ADSORBEN BERBAHAN FILTER ROKOK NON PAKAI UNTUK MENURUNKAN KADAR CO DAN NOx PADA ASAP ROKOK - Kawista Arum Kinanti; Novirina Hendrasarie (EnviroUS, 2021)
Air pollution does not only occur outside the room but also indoors. One of the most common indoor pollutants is Carbon Monoxide (CO) and Nitrogen Oxide (NOx). Incomplete combustion smoke accumulates in the room as a result of cigarette consumption. Pollutant reduction can be done by means of adsorption, this research utilizes capsule and charcoal non-use cigarette filter waste from cigarette filter-producing factories that do not pass the quality test to be used as activated carbon which will be used as CO and NOx adsorbents in cigarette smoke. After carbonization, the cigarette filter was activated with a KOH solution of 65% using an activator agent and solution ratio of 4: 1. This study used a reactor that was modeled like a room with a space volume of 0.02 m2. Activated carbon made from FR-Capule and FR-Charcoal is proven to be able to reduce CO levels by 86.8% in a contact time of 120 minutes and NOx 89.7% within 30 minutes of contact time on sidestream smoke, and the CO content drops by 98.8% while NOx decreased by 100% at 30 minutes of contact time on mainstream smoke.